Rhapsody Recent review - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Rhapsody. PALABRAS CLAVE: Rhapsody, Frederick Ashton, Patrick Caulfield.
Dentro del apartado "Dance Now. Recent reviews".